Susceptibility to Spirodiclofen in field populations of Tetranychus urticae (Acari: Tetranychidae) from strawberry plantations in Lima region, Peru - Flores-Bernedo, Juan (2020)
The use of inhibitors of lipids synthesis is among the available strategies for the control of Tetranychus urticae (Acari: Tetranychidae) in strawberry plantations. The study aimed to monitor the susceptibility to Spirodiclofen in field populations of T. urticae from strawberry plantations in Lima region, Peru. Adult T. urticae were collected from strawberry plantations in districts of Aucallama, Chancay, Huaral, and Santa Rosa de Quives in Lima region, Peru. A population collected from Acalypha wilkesiana in campus of the Universidad Nacional Agraria La Molina (UNALM), where chemical pesticide has never been applied, was used as a susceptible reference line. This reference line was subjected to toxicological bioassays to estimate the LC50 and LC95. Afterward, bioassays were conducted on the population using the LC50 and LC95 estimated for the susceptible reference line. The obtained data was subjected to one-way analysis of variance and mean comparison was done by Tukey test (α = 0.05). There were no significant differences between the four populations’ LC50 and LC95, with respect to the estimated susceptible reference line. This implies that the four studied populations of T. urticae are susceptible to Spirodiclofen, with no evident resistance problems. Therefore, Spirodiclofen is a useful tool for the control of T. urticae form strawberry plantations in the studied location. The factors that influenced the results are discussed in the present work.